Multi-level thematic map visualization using the Treemap hierarchical representation model - Zhou, Mengjie; Hu, Wenqing; Ai, Tinghua (Journal of Geovisualization and Spatial Analysis, 2020)
In the era of big data, a large volume of location-related semantic data needs to be visualized. The geographic information service needs to consider multi-level requests that can be adaptable to different users. Location-related semantic data can be represented in a thematic map. However, the traditional thematic map visualization can only visualize hierarchical information at one level using a statistical chart. This study presents a multi-level thematic mapping method that can visualize attribute information using LOD (Level of Detail) technology. We combine a Treemap with a cartogram to represent attribute information in thematic maps and build a LOD-Treemap model to realize multi-level visualization of attribute information. In the case study, we use our method to visualize and analyze the Chinese Farmers' Income Structure.